Correlation between placental histopathology and perinatal outcome in COVID-19 - Devendra Arora; K S Rajmohan; Sanjay Singh; Vinod Nair; Sanghita Barui; Madhusudan Dey; Abhijeet Kumar (Tzu Chi Medical Journal)
Objectives: An alarming rate of adverse perinatal outcomes as well as maternal deaths has been reported worldwide during this pandemic. It would be prudent to start thinking on the lines of acute or chronic intrauterine fetal hypoxia due to placental microvascular pathology or villitis caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection. Autopsy studies of deceased patients with severe COVID-19 have revealed the presence of diffuse pulmonary alveolar damage, thrombosis, and microvascular injuries. It is expected that similar pathological features such as microvascular injuries could be found in the placenta of infected pregnant women. Materials and Methods: Placentas of singleton pregnancies from 42 SARS-CoV-2 positive mothers delivered at term were submitted for histopathological examination. Those with multifetal gestation, hypertensive disorder, fetal growth restriction, structural or chromosomal anomalies in the fetus, thrombophilia, prolonged prelabor rupture of membranes, and placenta accreta spectrum were excluded from the study. Histopathological examination was done by two pathologists independently and only those results concurred by both were reported. Histopathological features and corresponding neonatal outcome were analyzed. Results: Reports of 42 placentas from patients with SARS-CoV-2, delivered at term (37–40 weeks) were analyzed in our study. Features of maternal vascular malperfusions (MVM) were present in 45% (n = 19) cases. Features of fetal vascular malperfusions (FVM) were present in 23.8% (n = 10) cases. There were 47.6% (n = 20) cases showing at least one feature of acute inflammatory pathology (AIP) and 42.8% (n = 18) showing features of chronic inflammatory pathology (CIP). Neonatal respiratory distress syndrome was found in 19% (n = 8) of the neonates. Correspondingly, nearly all placentas (n = 7) of these neonates showed features of MVM, FVM, AIP and CIP. There was no maternal or neonatal mortality in our study group. Conclusion: The main findings of our study include maternal as well as fetal vascular malperfusions and placental inflammatory pathology. These findings provide an outline for better understanding of etiological factors and pathogenesis of adverse perinatal outcomes in SARS-CoV-2 infection.